Understanding Western tourists in developing countries - Egmond, Antionius Nicolaas Francesco van, 1946- (CAB books., 2007)
Developing countries are increasingly reliant on tourism to generate income. To do this successfully it is critical for them to have an understanding of the tourist phenomenon. This book provides an overview of 'West-South' tourism, reviewing and evaluating theoretical perspectives as well as empirical studies of organized tours, and backpackers.